A multi‐disciplinary approach to the diagnosis and management of allergic diseases: An EAACI Task Force. Issue 1 (8th November 2021) - Vassilopoulou, Emilia; Skypala, Isabel; Feketea, Gavriela; Gawlik, Radoslaw; Dunn Galvin, Audrey; Meyer, Rosan; Pitsios, Constantinos; Maria Pop, Raluca; Ryan, Dermot; Said, Maria; Schiere, Sophie; Vlieg‐Boerstra, Berber; et al.
Abstract: Background: Guidelines for management of patients with allergic conditions are available, but the added value of nurses, allied healthcare professionals (AHPs), and general practitioners (GPs), in the management of allergic disease, has not been fully clarified. The European Academy of Allergy and Clinical Immunology (EAACI) appointed a task force to explore this issue. Aim: To investigate the added value of nurses, AHPs, and GPs in management of allergic diseases, in an integrated model of care. Methods: A search was made of peer‐reviewed literature published between 2010 and December 2020 (Cochrane Library, PubMed, and CINAHL) on the involvement of the various specific healthcare providers (HCPs) in the management of allergic diseases. Results: Facilitative models of care for patients with allergies can be achieved if HCP collaborates in the diagnosis and management. Working in multi‐disciplinary teams (MDT) can increase patients' understanding of the disease, adherence to treatment, self‐care capabilities, and ultimately improve quality of life. The MDT competencies and procedures can be improved and enhanced in a climate of mutual respect and shared values, and with inclusion of patients in the planning of care. Patient‐centered communication among HCPs and emphasis on the added value of each profession can create an effective integrated model of care for patients with allergic diseases. Conclusion: Nurses, AHPs, and GPs, both individually and in collaboration, can contribute to the improvement of the management of patients with allergic disease. The interaction between the HCPs and the patients themselves can ensure maximum support for people with allergies.